Promotional Strategies for Culinary Tourism in Enhancing Destination Image and Increasing the Revenue of Micro Enterprises in Wanayasa, Purwakarta - Komaladewi, Rita; Rhiswandi, Rhandi; Mulyani, Indah Putri; Setyadi, M. Aditya; Herdianie, Revalina (Jurnal Pengabdian Masyarakat, 2025)
Purpose: The service aims to highlight how various marketing strategies such as social media, food festivals and various local cultural bases can contribute. In the economic growth of the culinary sector according to the increase in the attractiveness of tourist destinations Method: This service uses an approach using direct observation to observe the social and economic conditions of the community and the dissemination of questionnaires to collect data on the needs and aspirations of residents. The results of the analysis are used to design the right solution for the target community. Practical Application: The results of this service can be a reference for local governments, business actors and local communities in designing more effective promotional strategies to increase the attractiveness of culinary tourism destinations. This growth is also beneficial for culinary micro business owners in optimizing the marketing of their products through social media and experience-based promotional activities such as Culinary Festivals and collaborations with influencers. Conclusion: Promotion strategies through social media and culinary festivals strengthen the image of the destination, increase tourist visits, and support the income of culinary micro businesses. Collaboration between the government, business actors, and local communities is needed to create sustainable marketing to develop culinary tourism in Wanayasa, Purwakarta.